Adverse Perinatal Outcomes at Advanced Pregnancy Ages: A Single Center Study - Osman Samet Gunkaya; Seher Koyuncu Aydın (Clinical and Experimental Obstetrics & Gynecology)
Background: Advanced maternal age (AMA) has been associated with various adverse obstetric, perinatal, and neonatal outcomes. This study primarily aimed to compare pregnancy outcomes in women aged 40 years and older with those aged 35–39 years, with a secondary aim to determine advanced maternal age by comparing these two age groups with those aged 20–34 years. Methods: This was a retrospective review of adults who gave birth between January 2020 and August 2024. All pregnant women in this study were single pregnancies and aged 20 years and older. Pregnant women using assisted reproductive technology and those with missing data were excluded from the study. This study included three groups of pregnant women: 20–34, 35–39, and 40 years and older. Perinatal outcomes of the three groups were compared. Results: AMA has previously been associated with various adverse obstetric outcomes. However, while there was a significant difference in birth weeks between the 20–34 years age group and the ≥40 age group (p = 0.019), the birth weeks of other age groups were similar. Moreover, there was no statistically significant difference between birth weights. Maternal ages of 35–39 and ≥40 years were associated with increased rates of cesarean delivery, pre-eclampsia, low birth weight, gestational diabetes mellitus (GDM), fetal growth restriction (FGR), preterm delivery, and low Apgar score (p < 0.001); however, rates of placental abruption, and preterm premature rupture of membranes (PPROMs) were similar to women aged <35 years. Gestational hypertension (GHT) (adjusted odds ratio (adjOR): 6.710, 95% confidence interval (95% CI): 2.755–16.343, p = < 0.001), oligohydramnios (adjOR: 2.145, 95% CI: 1.056–4.356, p = 0.035), macrosomia (adjOR: 5.459, 95% CI: 1.164–25.609, p = 0.031), and postpartum hemorrhage (adjOR: 5.139, 95% CI: 1.021–25.872, p = 0.047) are more common in women aged ≥40 years compared to both the reference group and the <35 age group. Conclusions: Adverse perinatal outcomes are more common in pregnant women aged 35 and over. These adverse outcomes are more common in the ≥40 years age group. To prevent these negative outcomes as well as potential maternal and fetal mortality and morbidity, we believe it is crucial to monitor these pregnant women closely during the prenatal period.